Partai Politik Islam dan Pemilihan Umum Studi Peningkatan Dukungan Elektoral PKB dan PPP Pada Pemilu Legislatif 2014 DPR RI di Dapil DKI Jakarta - Malik, Donie Kadewandana (Jurnal Politik Indonesia: Indonesian Political Science Review, 2016)
This study aimed to analyze the increase of voice support of Islamic parties (PKB and PPP) on Legislative Election 2014 House of Representative Republic of Indonesia in DKI Jakarta Constituency. Referring to the results of Legislative Elections on 2004 and 2009, PKB and PPP votes have significant decreased. However, political constellation changed in the 2014 election, votes of PKB and PPP have increased. The increase of electoral support of the majority of political parties on the legislative elections 2014, is a new phenomenon in the Reformation Era. Before 2014 election, there were predictions of analysts and institutions survey stated that the party vote-Islamic political party will be difficult to rise and tend to decline as in the 2004 and 2009 elections. But the forecast is not proven, the majority of Islamic political power has increased in the 2014 election. Therefore, this article will describe more about the factors causing the increase in electoral support of PKB and PPP on Legislative Election 2014 House of Representative Republic of Indonesia in DKI Jakarta Constituency